2003
DOI: 10.1103/physrevc.67.055207
|View full text |Cite
|
Sign up to set email alerts
|

Low-lyingS-wave andP-wave dibaryons in a nodal structure analysis

Abstract: The inherent nodal surface structure analysis approach is proposed for the sixquark clusters with u, d and s quarks. The wave-functions of the six-quark clusters are classified, and the contribution of the hidden-color channels are discussed.The quantum numbers and configurations of the wave-functions of the low-lying dibaryons are obtained. The states [ΩΩ] and the hidden-color channel ones with the same quantum numbers are proposed to be the candidates of experimentally observable dibaryons.It has been known… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Newborn strange stars could thus be solidified soon after supernova. The nature of this kind solid quark matter may depend on the quark cluster structures (Liu, Li, & Bao 2003) as well.…”
Section: Can Quark Matter Be Solid?mentioning
confidence: 99%
“…Newborn strange stars could thus be solidified soon after supernova. The nature of this kind solid quark matter may depend on the quark cluster structures (Liu, Li, & Bao 2003) as well.…”
Section: Can Quark Matter Be Solid?mentioning
confidence: 99%
“…These results are in similar lines and it also indicates that even binary phenomena like fission will also be insensitive towards isospin dependence of the dynamics [2]. Recently theoretical studies on the high density symmetry energy have been started by investigating heavy ion collisions of asymmetric systems [3,4]. Comparisons of collisions of neutron-rich to that of neutron-deficient systems provide a means of probing the asymmetry term experimentally [5][6][7].…”
Section: Introductionmentioning
confidence: 76%
“…Pairwise interesting are recent studies on proton-ptoton collisions, which revealed the presence of intermediate P-wave ΔN states with spin 0 and 2 at 2.197(8) and 2.201 (5) GeV respectively, see ref [96]. Although these states are not classified as dibaryons [97] because of their large decay width (Γ 100 MeV) [96,98], an attractive force appears to lower the expected energy of the Δ − N system by ≈ 30 MeV. Additionally, loosely bound binary compounds of hadrons appearing in the vicinity of a P-wave strong decay threshold are not forbidden by the theory of hadronic molecules [99].…”
Section: Preamblementioning
confidence: 98%
“…, (97) where D(E * ) is the strong P-wave coupling constant in presence of attractive electrostatic interaction and the matrix j C is, now, given by…”
Section: Attractive Channelmentioning
confidence: 99%